2013
DOI: 10.7705/biomedica.v34i0.1636
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilidad antibiótica de bacterias obtenidas de queratitis e infecciones intraoculares en la Fundación Oftalmológica de Santander (FOSCAL), Floridablanca, Colombia

Abstract: Acuña: redacción del artículo. Todos los autores participaron en el análisis de los datos y la revisión crítica del artículo. ARTÍCULO ORIGINAL Biomédica 2014;34(Supl. Introducción. La resistencia bacteriana es crítica para la selección de los antibióticos en el tratamiento de las infecciones, por ello es vital conocer su estado actual en nuestro medio. Objetivo. Determinar la sensibilidad antibiótica bacteriana in vitro obtenida de los cultivos de queratitis e infecciones intraoculares. Materiales y métodos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(21 reference statements)
1
7
0
5
Order By: Relevance
“…Comparing the findings for imipenem in the current study (resistance of 9.7% for Grampositives and 10% for Gram-negatives), it also showed an upsurge in its resistance rate, in comparison with the research conducted in our clinic with samples obtained between 2011 and 2012: resistance to imipenem with the Kirby-Bauer method was 1.1% among Gram-positive bacteria and 0% in Gram-Negatives [27].…”
Section: Discussionsupporting
confidence: 70%
“…Comparing the findings for imipenem in the current study (resistance of 9.7% for Grampositives and 10% for Gram-negatives), it also showed an upsurge in its resistance rate, in comparison with the research conducted in our clinic with samples obtained between 2011 and 2012: resistance to imipenem with the Kirby-Bauer method was 1.1% among Gram-positive bacteria and 0% in Gram-Negatives [27].…”
Section: Discussionsupporting
confidence: 70%
“…In vitro studies have shown excellent susceptibility of H. pylori strains to moxifloxacin [18], and clinical trials have confirmed its higher effectiveness -as a first-line therapycompared with standard clarithromycin-based triple therapy [19]. Furthermore, few studies have suggested that the emergence of bacterial resistance appears to be less common for moxifloxacin than for other fluoroquinolones, and that moxifloxacin may be less affected by quinolone resistance than levofloxacin in H. pylori [18] and other bacterial infections [20,21]. Therefore, the aim of the present study was to evaluate the efficacy and tolerability of a second-line triple regimen containing moxifloxacin in patients whose previous H. pylori eradication treatment failed.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies of polymicrobial infections have documented alterations in virulence factors, biofilm formation, and antibiotic resistance or tolerance [ 5 ]. While much research has focused on the pathogenesis of the polymicrobial nature of systemic infections, research on polymicrobial infections of the eye has been limited to studies reporting on the frequency of such infections in keratitis and/or endophthalmitis, with rates ranging from 2–50% [ 10 , 11 , 14 , 15 – 23 ], or as high as 83% for endophthalmitis using polymerase chain reaction amplification techniques [ 24 ].…”
Section: Introductionmentioning
confidence: 99%